2021
DOI: 10.1089/fpd.2020.2839
|View full text |Cite
|
Sign up to set email alerts
|

When Pet Snacks Look Like Children's Toys! The Potential Role of Pet Snacks in Transmission of Bacterial Zoonotic Pathogens in the Household

Abstract: Recent foodborne pathogen outbreaks associated with dry pet food and treats have focused the attention on these products as vehicles of pathogens for both pets and their owners. This study investigates the purchasing habits of dog owners and determines if and in what form pet snacks can be potentially dangerous for humans, especially for children. For these purposes, questionnaires collected from 406 dog owners were evaluated and microbiological analyses were performed on 120 dry pet snacks. The shape of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This may explain why pet ownership was not a risk factor in the perinatal group. Moreover, foodborne pathogen outbreaks associated with pet food have highlighted these products as vehicles for pathogens in both pets and their owners [ 33 ]. One study showed that presumptive Listeria species were detected in 64% of pet food product brands in Lebanon [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why pet ownership was not a risk factor in the perinatal group. Moreover, foodborne pathogen outbreaks associated with pet food have highlighted these products as vehicles for pathogens in both pets and their owners [ 33 ]. One study showed that presumptive Listeria species were detected in 64% of pet food product brands in Lebanon [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…An investigation also reported that more than 6% of respondents acknowledged incidents of involuntary ingestion of pet snacks, resulting in fever and gastrointestinal manifestations. In the cited study, children and infants are particularly vulnerable, as they are more likely to come into contact with pet snacks due to their toy-like appearance [ 33 ]. The upward trend in pet ownership and close contact between people and pets may also increase the likelihood of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a study evaluating the microbiological quality of dry pet snacks, the presence of L. ivanovii was reported in 1 among 120 samples analyzed, while the other 119 samples appeared in good sanitary condition [157]. It can be observed that the distribution of positivity rates was not very variable for different food categories, except for a few investigations reporting exceptionally high values.…”
Section: Milkmentioning
confidence: 92%
“…Finally, in a study evaluating the microbiological quality of dry pet snacks, the presence of L. ivanovii was reported in 1 among 120 samples analyzed, while the other 119 samples appeared in good sanitary condition [157].…”
Section: Milkmentioning
confidence: 97%
“…Finally, in a study evaluating the microbiological quality of dry pet snacks, the presence of Listeria ivanovii was reported in one among 120 samples analyzed, while the other 119 samples appeared in good sanitary condition [149].…”
Section: Dairy Productsmentioning
confidence: 97%